2020
DOI: 10.3389/fvets.2020.00439
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Analysis of the Development of Acquired Radioresistance in Canine and Human Mammary Cancer Cell Lines

Abstract: Research using in vitro canine mammary cancer cell lines and naturally-occurring canine mammary tumors are not only fundamental models used to advance the understanding of cancer in veterinary patients, but are also regarded as excellent translational models of human breast cancer. Human breast cancer is commonly treated with radiotherapy; however, tumor response depends on both innate radiosensitivity and on tumor repopulation by cells that develop radioresistance. Comparative canine and human studies investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 103 publications
1
9
0
Order By: Relevance
“…Because cancer cell lines over the course of cancer treatment tend to acquire resistance to therapy, we tested whether REV1 inhibition may sensitize acquired radioresistant cell lines to radiation treatment. To test this hypothesis, we treated isogenic pairs of cancer cells, including human breast cancer cells (ZR751 and its radioresistant counterpart ZR-751 RR) and canine mammary cancer cells (REM and its radioresistant counterpart REM RR) [ 19 , 20 ], with increasing doses of drug 5 (7587885), JH-RE-06, and JH-RE-06.NaOH at 1 and 10 μM. Our results demonstrated no significant differences in cytotoxicity in the radioresistant cell lines compared to their isogenic parental controls ( Figure 2 C and Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because cancer cell lines over the course of cancer treatment tend to acquire resistance to therapy, we tested whether REV1 inhibition may sensitize acquired radioresistant cell lines to radiation treatment. To test this hypothesis, we treated isogenic pairs of cancer cells, including human breast cancer cells (ZR751 and its radioresistant counterpart ZR-751 RR) and canine mammary cancer cells (REM and its radioresistant counterpart REM RR) [ 19 , 20 ], with increasing doses of drug 5 (7587885), JH-RE-06, and JH-RE-06.NaOH at 1 and 10 μM. Our results demonstrated no significant differences in cytotoxicity in the radioresistant cell lines compared to their isogenic parental controls ( Figure 2 C and Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…CMT cells frequently show myoepithelial proliferation leading to preinvasive carcinoma (58,59). CMT-1026 is also a well-established basal like subtype cell line (60). Comparative pre-clinical studies of CMT-1026 and IPC-366 cell lines may be possible in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In general, there is a lack of radioresistant model systems to facilitate elucidating the mechanisms underlying the development of radioresistance. In our lab, we previously developed and extensively characterised novel in vitro radioresistant cell lines from human breast cancer (MCF-7, ZR-751 and MDA-MB-231) and canine mammary carcinoma (REM-134) cell lines [26,36]. We found that the radioresistance phenotype was maintained long term, even in the absence of radiation exposure, and concluded that the acquisition of radioresistance was not transient [26].…”
Section: Discussionmentioning
confidence: 99%